Cool infographics: effective communication with data visualization and design - Krum, Randy (Wiley, 2013)
Make information memorable with creative visual design techniques Research shows that visual information is more quickly and easily understood, and much more likely to be remembered. This innovative book presents the design process and the best software tools for creating infographics that communicate.